2019
DOI: 10.1002/pra2.76
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Open Access to Information: A Community Approach to Open Education and Open Textbooks

Abstract: Access to information as a necessary precondition for human flourishing is recognized explicitly in the UNESCO Strategic Development Goals, and mirrored by the work of universities globally to reduce barriers to information, especially research outputs. Growing international attention has turned to learning and teaching resources, particularly textbooks as a key barrier to fully engaging with, and participating in, higher education. The affordances of open texts provide an alternative to commercially published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…It would also help achieve the United Nations' sustainable development goals (UNESCO, 2016). Open education textbooks may contribute to education by providing students and lecturers with flexibility conceptualized as the “5 R's”, namely the ability to retain, reuse, repurpose, remix, and revise the resources (Cobb, 2018; Stagg and Partridge, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It would also help achieve the United Nations' sustainable development goals (UNESCO, 2016). Open education textbooks may contribute to education by providing students and lecturers with flexibility conceptualized as the “5 R's”, namely the ability to retain, reuse, repurpose, remix, and revise the resources (Cobb, 2018; Stagg and Partridge, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Open Educational Practices (OEP) are also evolving, supporting the opening and sharing of educational processes, and new collaborations between students and lecturers emerge, with the goal of improving access and empowering learners (Cronin and MacLaren 2018). New formats, such as open, connected courses (enabling students to connect with students and educators in other institutions and countries) and co-creation of open textbooks with students (Stagg and Partridge 2019), are also evolving. The learning theory promoted by George Siemens (2005) and Stephen Downes (2010) titled 'connectivism' looks at learning that takes place online across peer networks.…”
Section: Collaborative Developments In Educationmentioning
confidence: 99%
“…These challenges are explored by previous studies that have examined enablers of community engagement. For example, Wang and Wang (2017) and Stagg and Partridge (2019) examined a community-based approach to foster the adoption of open textbooks into the curriculum. Their findings indicated that a deliberate strategy is needed with a dual focus on a supportive learning space for teachers to have discussions, generate ideas and to experiment with open textbooks, and on the role of facilitators to organize structured meetings and to connect teachers' needs with information and expertise within the institute.…”
Section: Towards Sustainable Oer Communitiesmentioning
confidence: 99%